1992
DOI: 10.1002/zaac.19926100110
|View full text |Cite
|
Sign up to set email alerts
|

Beiträge zu den Eigenschaften von Titanaten mit Ilmenitstruktur. II. Zur Thermodynamik und elektrischen Leitfähigkeit von NiTiO3 und anderen oxidischen Phasen mit Ilmenitstruktur

Abstract: NiTiO3 zeigt bei hohen Temperaturen einen Phasenübergang mit einer kritischen Temperatur von ca. 1290°C. Durch EMK‐Messungen mit Hilfe der galvanischen Festkörperkette Ni,Tio2, NiTiO3|ZrO2/(+CaO)|Ni,NiO wurde die Standardreaktionsenthalpie bzw. ‐entropie der Reaktion NiO + TiO2 = NiTiO3 ober ‐ bzw. unterhalb des Phasenübergangs bestimmt. Die daraus ermittelte molare Umwandlungsenthalpie beträgt 18 ± 2 kJmol−1, die molare Umwandlungsentropie 12 ± 1 JK−1mol−1. Für einen angenommenen Ordnungs‐Unordnungsübergang f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
1

Year Published

1992
1992
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 9 publications
1
12
1
Order By: Relevance
“…[17] According to the DTA results obtained in this study, shown in Figure 5, NiTiO 3 (ilm) probably undergoes an order-disorder type of transformation. The critical transformation temperature obtained in this study (T c ϭ 1568 ‫ע‬ 2 K) is in good agreement with that reported by Lerch and Laqua [13] (T c ϭ 1563 K) from the DTA measurements.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…[17] According to the DTA results obtained in this study, shown in Figure 5, NiTiO 3 (ilm) probably undergoes an order-disorder type of transformation. The critical transformation temperature obtained in this study (T c ϭ 1568 ‫ע‬ 2 K) is in good agreement with that reported by Lerch and Laqua [13] (T c ϭ 1563 K) from the DTA measurements.…”
Section: Discussionsupporting
confidence: 92%
“…However, from the conductivity and electrochemical measurements, [13] the transition temperature is equal to 1538 K, which is 30 K lower than that obtained in the present investigation.…”
Section: Discussioncontrasting
confidence: 77%
See 3 more Smart Citations